Aquatic invertebrate community structure and functions within a Ramsar wetland of a premier conservation area in South Africa. (April 2023) - de Necker, Lizaan; Dyamond, Kelly; Greenfield, Richard; van Vuren, Johan; Malherbe, Wynand
Graphical abstract: Highlights: Makuleke Wetlands receive water from rivers influenced by anthropogenic inputs. Multivariate macroinvertebrate analyses to assess ecosystem structure and function. Aquatic biodiversity was some of the highest recorded in the Global South. Wetland ecosystem structure is in a suitable condition to support high biodiversity. Invasive species threaten native biodiversity in this premier conservation area. Abstract: The Ramsar-accredited Makuleke Wetlands are located in the Makuleke Concession in the northern Pafuri region of the Kruger National Park in South Africa. The Pafuri area holds up to 75% of Kruger National Park's total biodiversity, emphasising the Makuleke Wetlands' international environmental importance. The Makuleke Wetlands are composed of the floodplains of the Luvuvhu and Limpopo rivers, with an estimated 31 wetlands present within the floodplains. Ten floodplain wetlands were assessed in the Makuleke region, eight of which are fed by the Limpopo River and the other two from the Luvuvhu River. Water and aquatic invertebrate communities were sampled at each site during surveys in April and September 2015 to provide baseline information on the aquatic biota of this Ramsar site. Multivariate data analytical techniques were used to assess the role of season and water quality in structuring the aquatic invertebrate communities of the wetlands. Macroinvertebrate functional feeding group ratios were also calculated as an indication of wetland ecosystem structure and function. Aquatic invertebrate diversity was some of the highest recorded for wetlands in South Africa, indicating the important role these habitats play in supporting high biodiversity in the Makuleke region. Worryingly, one of the most prolific invasive molluscan species, Tarebia granifera, was present in the wetlands and is a significant threat to native biodiversity of this conservation area. Community characteristics and ecosystem structure and function of the aquatic invertebrates further indicated that the Makuleke Wetland habitats were of good quality and provided a sufficient stable substrate for all aquatic invertebrates. Functionally, the system was characterised as reliant on heterotrophic inputs as autotrophic sources are limited. This is the first study of its kind for the region and lays the groundwork for future ecosystem studies on these important wetlands in the second-largest floodplain of South Africa.